Obesity and rates of clinical remission and low MRI inflammation in rheumatoid arthritis. Issue 10 (12th June 2017) - George, Michael D; Østergaard, Mikkel; Conaghan, Philip G; Emery, Paul; Baker, Daniel G; Baker, Joshua F
Abstract : Objectives: Obesity has been proposed as a risk factor for refractory rheumatoid arthritis (RA). We evaluated the impact of obesity on achieving clinical and imaging definitions of low disease activity. Methods: This study evaluated 470 patients with RA from GO-BEFORE and GO-FORWARD randomised clinical trials. Included patients had blinded clinical disease activity measures and MRI at baseline, 24 and 52 weeks. Synovitis, osteitis and total inflammation scores were determined using the RA MRI scoring system. Multivariable logistic regression analyses compared odds of achieving Disease Activity Score using 28 joints and C-reactive protein (DAS28-CRP) remission, low component measures, or low MRI inflammation measures at 24 weeks in patients with obesity versus no obesity. Results: At 24 weeks, patients with obesity were significantly less likely to achieve DAS28(CRP) remission (OR 0.47; 95% CI 0.24 to 0.92, p=0.03). In contrast, patients with obesity had similar odds of achieving low synovitis (OR 0.94; 95% CI 0.51 to 1.72, p=0.84) and inflammation scores (OR 1.16; 95% CI 0.61 to 2.22, p=0.64) and greater odds of achieving low osteitis scores (OR 2.06; 95% CI 1.10 to 3.84, p=0.02) versus normal weight patients. Conclusions: Patients with RA and obesity have lower rates of DAS28 remission but similar rates of low MRI activity compared with patients without obesity, suggesting that obesity and its associated comorbidities can bias clinical disease activity measures. Trial registration number: NCT00361335 and NCT00264550 ; Post-results.